Maternal vitamin D deficiency and its effects on pregnancy outcomes - Ibrahim, Yakubu; Mohd Jamil, Amilia Afzan; Nordin, Norshariza; Loh, Su Peng; Basri, Nurul Iftida (John Wiley and Sons, 2026)
Vitamin D deficiency remains a global health concern for pregnant women. Adequate vitamin D is vital for optimal fetal development, immune regulation, and preventing adverse pregnancy outcomes. This study aims to determine the impact of vitamin D deficiency on pregnancy complications among a Malaysian cohort. This was a prospective observational study involving 414 pregnant women. Data was collected using a structured interviewer-administered questionnaire, including sociodemographic and anthropometric characteristics, vitamin D risk factor assessment questions, vitamin D status, and follow up for pregnancy outcomes. Serum vitamin D level was determined using electrochemiluminescence immunoassay (ECLIA). The prevalence of vitamin D deficiency was 64.7%. Participants' daily median total vitamin D intake was 11.2 μg/day which was significantly low compared with the vitamin D recommended nutrient intake (RNI) of the study population. The study found a significant association between vitamin D status and pregnancy complications: gestational hypertensive disorder (ꭓ2 = 9.024; p = 0.011), preterm birth (ꭓ2 = 8.249; p = 0.016), and Group B Streptococcus carrier (ꭓ2 = 7.379; p = 0.025). Participants who reported vitamin D consumptions during pregnancy had decreased likelihood of gestational hypertensive disorders (aOR = 0.278 (0.08–4.79) 95% CI; p = 0.0001), Group B Streptococcus carriage (aOR = 0.282 (0.08–0.99) 95% CI; p = 0.048), and decreased likelihood of cesarean section (aOR = 0.580 (95% CI: 0.347–0.967); p = 0.037). Vitamin D deficiency was significantly associated with increased risk of gestational hypertensive disorders, Group B Streptococcus carriage and cesarean section. It can be suggested that maternal vitamin D deficiency might be associated with an increased risk of some adverse pregnancy outcomes. Further interventional research is required to confirm a causal relationship, meanwhile promoting adequate vitamin D status among pregnant women may be beneficial.